MAPPING INTEGRATIVE GREEN JOBS STRATEGIES IN TOURISM TVET CURRICULUM: A BIBLIOMETRIC ANALYSIS - Bimo Kuncoro Jati; Riswano; Rachmadina Rafika Triani; Kezia Elsty; Meisya Anggraini; Candra Karismawan (RADJA PUBLIKA, 2026)
Sustainability has become a priority for the global tourism industry, requiring a workforce equipped with green skills. However, the integration of these competencies within Technical and Vocational Education and Training (TVET) remains fragmented. This study aims to map the scientific evolution of research regarding sustainable tourism competencies in vocational education. Using a bibliometric approach, data was retrieved from Google Scholar, then analyzed using VOSviewer and Biblioshiny. The results demonstrate a significant upward trend in publications from 2015 to 2025. Key research clusters center on